Comparing the Effects of Automat Use on Assembly Line Performance in the Apparel Industry by Using a Simulation Method - KAYAR, MAHMUT (INST CHEMICAL FIBRES, 2015)
In this article, general information related to efficiency, assembly lineS and simulation are primarily reviewed. previous studies on assembly line balancing are theoretically analysed. Thereafter two different assembly lines are designed to produce jean trousers. In one assembly line - manual machines and in another automats are used for seven selected operations. These assembly lines are modelled by the Promodel Simulation Program and the assembly line balancing problem is applied. The aim of the study is to establish which assembly lines have the highest line performance and to research the effects of using automat in assembly lines on production volume and efficiency. The simulation method formerly informs investors about the consequences of their investment in the decision making process for technology investments. The study concludes that automat usage on an assembly line increases the production volume and affects the efficiency of assembly line positively.
Keywords: jean trousers; assembly line balancing; automat; simulation; CLOTHING INDUSTRY; BALANCING METHODS; WORK